Convergence Analysis for a System of Generalized Equilibrium Problems and a Countable Family of Strict Pseudocontractions. (4th January 2011) - Cholamjiak, Prasit; Suantai, Suthep
Abstract : We introduce a new iterative algorithm for a system of generalized equilibrium problems and a countable family of strict pseudocontractions in Hilbert spaces. We then prove that the sequence generated by the proposed algorithm converges strongly to a common element in the solutions set of a system of generalized equilibrium problems and the common fixed points set of an infinitely countable family of strict pseudocontractions.